2009
DOI: 10.1267/ahc.08012
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Adenylate Kinase 4 in Mouse Tissues

Abstract: Adenylate kinase (AK) is a key enzyme in the high-energy phosphoryl transfer reaction in living cells. Of its isoforms, AK4 has a similar sequence and subcellular localization to that of AK3 in the mitochondrial matrix. However, unlike AK3, AK4 lacks the guanosine triphosphate: adenosine monophosphate phosphotransferase activity. To elucidate the physiological role of AK4, we explored the protein localization of AK4 in various mouse tissues by immunohistochemical analysis. AK4 protein was detected in the kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…AK4 (adenylate kinase 4) was responsible for cell proliferation, differentiation and cytoskeleton formation[ 34 ]. AK4 catalyzed the reversible transfer of adenosine triphosphate (ATP) or guanosine triphosphate (GTP) to adenosine monophosphate (AMP), and it played a key role in high-energy phosphoryl transfer and consumption of ATP and GTP[ 35 ]. AK4 was also an essential enzyme in energy metabolism in the cytosol, mitochondria and nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…AK4 (adenylate kinase 4) was responsible for cell proliferation, differentiation and cytoskeleton formation[ 34 ]. AK4 catalyzed the reversible transfer of adenosine triphosphate (ATP) or guanosine triphosphate (GTP) to adenosine monophosphate (AMP), and it played a key role in high-energy phosphoryl transfer and consumption of ATP and GTP[ 35 ]. AK4 was also an essential enzyme in energy metabolism in the cytosol, mitochondria and nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AK4 contains an N-terminal mitochondrial import sequence which mediates localization to the mitochondrial matrix ( 14 ). AK4 is widely expressed in multiple types of tissues such as kidney, heart and liver ( 15 ). AK4 was also reported to participate in protection from oxidative stress ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…AK2 is essential for growth in D. melanogaster [ 2 ] and a genetic AK2 deficiency in human causes reticular dysgenesis and sensorineural deafness [ 3 , 4 ], indicating the important role of AK2 in hematopoietic differentiation as well as development of auditory organ. Until now, we have studied the structure and function of AK isozymes and reported that they play important roles in cellular energy metabolism [ 2 , 5 8 ]. We also reported that the therapeutic efficacy of iron chelator, deferoxamine (DFO) for treating hepatocellular cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%